2014
DOI: 10.1159/000362717
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bullous Pemphigoid Disease Area Index during Treatment: A Prospective Study of 30 Patients

Abstract: Background: Recently, a consensus Bullous Pemphigoid Disease Area Index (BPDAI) was proposed to measure therapeutic outcomes in bullous pemphigoid (BP). Objective: To compare BPDAI with other clinical parameters of disease activity at baseline and to describe the variations of BPDAI during the initial phase of treatment. Methods: Thirty BP patients were included and followed for 1 year. BPDAI was assessed at baseline and on days 30, 90 and 360 by the same investigator. Concomitantly, the number of daily new bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…Anti-BP180, but not anti-BP230, titres has been established to correlate well with disease activity (12)(13)(14). Another study, conducted in France (15), found good correlation of BPDAI with clinical parameters of disease activity and proposed a cut-off value of 56 for severe BP.…”
mentioning
confidence: 99%
“…Anti-BP180, but not anti-BP230, titres has been established to correlate well with disease activity (12)(13)(14). Another study, conducted in France (15), found good correlation of BPDAI with clinical parameters of disease activity and proposed a cut-off value of 56 for severe BP.…”
mentioning
confidence: 99%
“…Baseline severity data were available for 67.17% (352 of 524) of cases. There have been several studies considering objective scoring systems for bullous diseases including BP, but there is no published standardized severity scoring system available . Therefore, a measure of severity was suggested as part of the audit as a means of standardizing interpretation across centres; this was primarily based on the number of blisters.…”
Section: Resultsmentioning
confidence: 99%
“…There have been several studies considering objective scoring systems for bullous diseases including BP, but there is no published standardized severity scoring system available. 5,6 Therefore, a measure of severity was suggested as part of the audit as a means of standardizing interpretation across centres; this was primarily based on the number of blisters. Of the 352 patients, 63.9% (225 of 352) had a recorded baseline severity of very mild (< 3 blisters), 21.9% (77 of 352) mild (3-9 blisters), 8.8% (31 of 352) moderate (10-30 blisters) and 5.4% (19 of 352) severe (> 30 blisters).…”
Section: Patient Populationmentioning
confidence: 99%
“…ABSIS = Autoimmune Bullous Skin Disorder Intensity Score; BPDAI = Bullous Pemphigoid Disease Area Index; CDASI = Cutaneous Dermatomyositis Disease Area and Severity Index; CLASI = Cutaneous Lupus Erythematosus Disease Area and Severity Index; EBDASI = Epidermolysis Bullosa Disease Activity and Scarring Index; EASI = Eczema Acvitity and Scarring Index; MCID = minimal clinically-important difference; PASI = Psoriasis Area and Severity Index; PDAI = Pemphigus Disease Area Index; SCORAD = Scoring Atopic Dermatitis. 1 Rahbar et al, 2014; 2 Murrell et al, 2008; 3 Boulard et al, 2016; 4 Shimizu et al, 2014, 5 Pfutze et al, 2007; 6 Gourraud et al, 2012; 7 Puzenat et al, 2010; 8 Tofte et al, 1998; 9 Hanifin et al, 2001; 10 Breuer et al, 2004; 11 Schram et al, 2012; 12 Sartorius et al, 2010; 13 Loh et al, 2014; 14 Jain et al, 2016; 15 Wijayanti et al, 2014, Wijayanti et al, 2016; 16 Murrell et al, 2012; 17 Patsatsi et al, 2012; 18 Lévy-Sitbon et al, 2014; 19 Bonilla-Martinez et al, 2008; 20 Albrecht et al, 2005; 21 Klein et al, 2011; 22 Goreshi et al, 2012; 23 Anyanwu et al, 2015; 24 Stalder et al, 1993; 25 Schram et al, 2012; 26 Angelova-Fischer et al, 2005; 27 Langley and Ellis, 2004; 28 Zhao et al, 2015.…”
Section: Figmentioning
confidence: 99%